Програмні засоби обліку фондів шкільної бібліотеки - Сєров, Юрій; Ковальчук, Марина (Видавництво Львівської політехніки, 2013)
The article explores the main purpose of automation of the accounting of school library funds. It also considers a functional model for solving the problem and describes the process of developing the database.
Keywords: шкільна бібліотека; бібліотечний фонд; програмний засіб; модель; база даних